Respuesta :
Answer:
• from first principles rule:
[tex]{ \boxed{ \bf{ \frac{ \delta y}{ \delta x} = {}^{lim _{x} } _{h \dashrightarrow0} \: \frac{f(x + h) - f(x)}{h} }}}[/tex]
• f(x) → (csc x)^½
• f(x + h) → {csc (x + h)}^½
[tex]{ \rm{ \frac{ \delta y}{ \delta x} = {}^{lim _{x} } _{h \dashrightarrow0} \: \frac{ \{\csc(x + h) \} {}^{ \frac{1}{2} } - (\csc x ) {}^{ \frac{1}{2} } }{h} }} \\ \\ \hookrightarrow \: { \tt{rationalise : }} \\ \\ = { \rm{{}^{lim _{x} } _{h \dashrightarrow0} \: \frac{ \csc(x + h) - \csc x }{h \{ \{\csc(x + h) \} {}^{ \frac{1}{2} } + ( \csc x) {}^{ \frac{1}{2} } \} } }} \\ \\ = { \rm{{}^{lim _{x} } _{h \dashrightarrow0} \: \frac{1 - (\sin (x + h))( \csc x)}{h \{ \sin(x + h) \} \{ \csc(x + h) \} {}^{ \frac{1}{2} } \{ \csc x \} {}^{ \frac{1}{2} } }}} \\ \\ = { \rm{ = { \rm{{}^{lim _{x} } _{h \dashrightarrow0} \: \frac{1 - ( \sin(x) \cos(h) + \cos(x) \sin(h)) \csc x }{h \{ \sin(x + h) \} \{ \csc(x + h) \} {}^{ \frac{1}{2} } \{ \csc x \} {}^{ \frac{1}{2} } }}} }} \\ \\ = { \rm{ = { \rm{{}^{lim _{x} } _{h \dashrightarrow0} \: \frac{1 - \cos(h) + \cot(x) \sin(h) }{h \{ \sin(x + h) \} \{ \csc(x + h) \} {}^{ \frac{1}{2} } \{ \csc x \} {}^{ \frac{1}{2} } }}} }} \\ \\ { \tt{but : \sin(h) \approx h}} \\ { \tt{ : \cos(h) \approx 1 }} \\ \\ = { \rm{{{}^{lim _{x} } _{h \dashrightarrow0 \: } \: \frac{h \cot(x) }{h \{ \sin(x + h) \} \{ \csc(x + h) \} {}^{ \frac{1}{2} } \{ \csc x \} {}^{ \frac{1}{2} } } }}} \\ \\ { \tt{h \: tends \: to \: 0}} \\ \\ { \boxed{ \rm{ \frac{dy}{dx} = - \frac{1}{2 \sqrt{ \cot(x) \csc(x) } } }}}[/tex]